ADAB PESERTA DIDIK MENURUT IMAM AN-NAWAWI DALAM KITAB ATTIBYAAN FII AADAABI HAMALAT AL-QUR’AN - Budiman, Wandi (TADBIR MUWAHHID, 2017)
Adab has an important role for human life, so that became one of the manners of the Prophet's mission in this world. Adab is also one aspect of the Indonesian national education goals. Learners as those who are seeking knowledge should make adab as a handle in the education process, so that the knowledge learned into useful knowledge. The problem of adab has great attention over time, scholars, including Imam an-Nawawi. Through the book at-Tibyaan Fii ÉdÉbi hamalat al-QurÉn, Imam an-Nawawi discusses some points of adab that must be possessed by a learner in his education.